Buyer Behavior in Quality‐Dominated Multi‐Sourcing Recyclable‐Material Procurement of Green Supply Chains. Issue 3 (24th September 2014) - Sheu, Jiuh‐Biing
Abstract : This study presents a multi‐methodological approach to investigate buyer behavior in quality‐dominated multi‐sourcing recyclable‐material procurement of green supply chains. This work hypothesizes the correlations between buyer perceptions of supply and relational quality, quality attitude, psychological benefits, and willingness to pay. This is followed by conducting a normative analysis, where the postulated hypotheses are incorporated into a buyer behavior model which characterizes buyer decisions regarding multi‐supplier selection and price negotiations using multinomial logit model and Nash bargaining game theory. Through an empirical study, this work demonstrates that the proposed buyer behavior theory and hypotheses hold, and upport the analytical results yielded from the normative analysis. Analytical results indicate that supply‐ and relationship‐quality positively affect buyer quality attitude in the rational and affective cognition domains, and thus jointly determine buyer decisions regarding supplier selection and price negotiations in multiple sourcing green procurement. Nevertheless, the aforementioned effects are moderated by buyer psychological benefits. Additionally, this study demonstrates a phenomenon known as "buyer's supply surplus", which articulates the negative effect of buyer attitude towards channel relationship quality on willingness to pay. This can also rationalize why a buyer favors choosing suppliers with superior relational quality for the achievement of lower negotiated prices.